2012
DOI: 10.1016/j.ajo.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Delay to Treatment and Visual Outcomes in Patients Treated With Anti-Vascular Endothelial Growth Factor for Age-Related Macular Degeneration

Abstract: PURPOSE To investigate the potential influences that affect visual acuity (VA) outcome in a clinic-based cohort of age-related macular degeneration (AMD) patients undergoing anti–vascular endothelial growth factor (anti-VEGF) treatment for choroidal neovascularization. DESIGN Prospective interventional case series. METHODS Patients with subfoveal choroidal neovascularization (CNV) secondary to AMD were prospectively recruited. A detailed questionnaire was given to patients at time of enrollment, to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 14 publications
3
94
0
11
Order By: Relevance
“…The degree of change in VA is contingent on the baseline acuity, that is, at the time-point at which treatment is initiated. 16,[19][20][21] It is intuitive to suppose that treatment given when the disease has not caused permanent destruction of the neural and supporting cells will result in best outcomes. Morphological changes precede the loss of visual function.…”
Section: Parameters Used To Assess Response To Anti-vegf Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of change in VA is contingent on the baseline acuity, that is, at the time-point at which treatment is initiated. 16,[19][20][21] It is intuitive to suppose that treatment given when the disease has not caused permanent destruction of the neural and supporting cells will result in best outcomes. Morphological changes precede the loss of visual function.…”
Section: Parameters Used To Assess Response To Anti-vegf Therapiesmentioning
confidence: 99%
“…72 Delay in commencing treatment from symptom/disease onset has a detrimental effect on the outcomes of treatment of n-AMD with ranibizumab. 20 Each patient with n-AMD, however, needs to be managed with an individualised treatment plan. This requires follow-up at regular monthly intervals, and treatment as necessary.…”
Section: Management Of Suboptimal Response To Anti-vegf Therapy In Amdmentioning
confidence: 99%
“…A recent study by Lim and co-worker showed that delayed intervention leads to insufficient treatment, irreversible macular damage, and a poorer visual outcome. 9 In their study, a delay of 14 weeks doubled the likelihood for the worsening of vision after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is difficult to demonstrate because assessment of treatment delay relies on information provided by the patients, who are often uncertain of when the symptoms appeared; additionally, symptom awareness depends on the visual acuity of the fellow eye. This difficulty is even greater in retrospective studies, because treatment delay is frequently not reported by clinicians in a standardized manner [10], as has been shown by our study. Thus, the interval between onset of symptoms and first anti-VEGF injection is usually not analyzed in clinical trials [10] and is not adequately evaluated by retrospective studies.…”
Section: Discussionmentioning
confidence: 66%
“…This difficulty is even greater in retrospective studies, because treatment delay is frequently not reported by clinicians in a standardized manner [10], as has been shown by our study. Thus, the interval between onset of symptoms and first anti-VEGF injection is usually not analyzed in clinical trials [10] and is not adequately evaluated by retrospective studies. On the other hand, a prospective, clinic-based study, which evaluated visual outcomes after 6 months of anti-VEGF treatment, demonstrated that longer treatment delay from first symptoms of CNV was, in multivariate analysis, a highly significant predictor of adverse visual outcome, by limiting the ability to gain vision with treatment [10].…”
Section: Discussionmentioning
confidence: 66%